Imam Al-Ghazali's Perspective Moral Education : Pendidikan Akhlak Perspektif Imam Al-Ghazali - Ilham Aly Muhsi; Ainun Nadlif (Academia Open, 2021)
This article aims to find ethical education in Imam Al-Ghazali's attitude, so that the knowledge of the ethical school is more diverse and more comprehensive. The study technique used is a literature study, the information of which is obtained from a literature review with theoretical and philosophical techniques. Imam Al-Ghazali's moral perspective which is applied to Islamic education today can foster good and well-done values.